SAT0608 MRI of the Hand in Palyndromic Rheumatism: A Study with Dedicated-Extremity MRI. (9th June 2015) - Barbieri, F.; Ambrosetti, E.; Tomatis, V.; Aleo, E.; Migone, S.; Prono, V.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Palyndromic rheumatism (PR) was first described in 1944 by Hench and Rosenberg, as a peculiar form of intermittent arthritis. The possibility that PR may represent an early phase of rheumatoid arthritis (RA) has been debated. The observation that PR patients frequently show positive anti- citrullinated peptide antibodies (ACPA) is in keeping with this hypothesis. MRI findings in PR patients have been described only in anecdotal cases, although this technique could contribute to understand which subtype of PR can eventually evolve in RA. Objectives: To evaluate by extremity-dedicated MRI of the hand and wrist the lesions present in patients with PR. Methods: 15 patients seen in the period 2009-2013 and affected by palindromic rheumatism according to the criteria by Guerne et al were studied. 12 of them were women and mean age was 56.4±14 years. Median disease duration calculated between disease onset and MRI was 11 months (range 1-276 months); in the patient with disease duration of only one month the diagnosis was confirmed at follow-up. The median number of arthritis attacks was 4 (range 2-40) and the mean number of involved joints was 6.6±2.6. At the time of MRI, 12/15 patients had active arthritis of the hand or wrist. IgM rheumatoid factor was present in 8/15 (53%) patients and ACPA in 14/15 (93%). MRI was performed with a 0.2T extremity dedicated machine (Artoscan C, Esaote, Genova, Italy) using pre and post-contrast Turbo 3D (synovitis and erosions) and STIR (BME) sequences: Turbo 3D T1-weighted sequences (TR/TE=35/16 ms; matrix=192x160; FOV=140x140; slice thickness 0.8 mm; interslice gap 0 mm) in the coronal plane with subsequent reconstruction of the remaining planes; coronal and axial STIR sequences (TR/TE=1500/24 ms [coronal] and 2400/24 [axial]; matrix=192x160 [coronal] and 192x144 [axial]; FOV=160x160; slice thickness 3 mm [coronal] and 4 mm [axial]; interslice gap 0.3 mm [coronal] and 0.4 mm [axial]). MRI changes were graded according to RAMRIS. Results: Wrist synovitis was present in all studied patients and exceeded a score 3 in 8 (53%). Metacarpophalangeal (MCP) joints synovitis was seen in only 2 (13%) patients. Erosions of the wrist were seen in 7 (47%) patients but were minor (score =1) in the majority (4 patients). The scaphoid bone was most frequently affected. Erosions of the MCP joints were present in 4 (27%) patients. Bone marrow oedema (BME) was seen in 2 (13%) patients at the wrist and in one (7%) at the MCP joints. There was no significant correlation between MRI lesions and clinical and laboratory parameters, although patients with longer disease duration tended to show more often BME and those with elevated CRP to have a higher erosion score (both p=0.06). RAMRIS was similar in the active and inactive patients. Conclusions: This study is the first to describe the MRI findings of a small cohort of PR patients. The observation that synovitis is present in the totality of patients, irrespective of the presence of an actual acute attack, suggests that subclinical synovitis could persist also in the intercritical period. Conversely, BME and erosions were unfrequent, especially if compared to RA. Long-term follow-up studies are needed to understand if these last features can predict the evolution in overt RA. Disclosure of Interest: None declared